“Somewhere our belonging particles / believe in us.” A study of absentist language in the poetry of W.S. Graham - Nazargahi, Iran (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
The Heideggerian concept of “authentic language” and “inauthentic language” along with ‘inadequacy’, ‘indeterminacy’, fragmentation’ and ‘silence’ in the language of modern poetry, leads us to the crises of language. Martin Heidegger, the Existentialist philosopher, claims that poetry is the essence of language and language is the essence of being. While truth is the essence of the work of art, poetry as a creative work of art must deal with truth. The truth, which modern poetry deals with, is the isolation of man and the crises of identity that shows itself in the language. Thus “Absentist Poetry”claims that poetry, language and being, the three pillars of our existence are in crisis. Absentist language in the poetry of W.S. Graham is an answer to one of the most important struggles of poetry, the question of marginalization of modern poetry by the domination of fiction in the twentieth century. It also sheds light on the inadequacies of language and consequently, deals with the problem of identity in modern life. This paper attempts to introduce Absentist language, as a reason for the crises of identity of the modern man on one side and the marginalization of modern poetry on the other side.